Health screening: program ilmuan Majlis Profesor Negara bersama penduduk Sarawak - Francis, Frannelya; Shamsudin, Nur Haslina; James, Shreen Senara (Universiti Teknologi MARA, Sarawak, 2016)
As for the students and staff, this health screening activity was a golden opportunity to practise their knowledge and skills on the local community besides improving the communication skills with the public and boosting their confidence when liaising with the organisers and villagers. Furthermore, this programme has increased the awareness about the importance of giving back to the community and reaching out to those who are staying far from healthcare facilities.